Odpowiedzi

2010-02-14T15:48:04+01:00
X+2y=5 -> x=5-2x
3x-y=1
3x-y=1
3(5-2x)=1
15-6x=1
-6x=-14 |:(-6)
x=2,33
Najlepsza Odpowiedź!
2010-02-14T15:56:31+01:00
A)
x+2y=5
3x-y=1/*2

x+2y = 5
6x-2y = 2
________
7x = 7/:7
x = 1
3*1 -y = 1

x=1
3-y=1/-3

x=1
-y = -2/*(-1)

x=1
y=2

b)
x+7y=6
½x-2,4y=3/*(-2)

x+7y=6
-x+4,8y=-6
__________
11,8y = 0/:11,8
y = 0

x+0 = 6
x=6
y=0

c)
2(x-1)-3(1-y)=-y-1
x+y=5

2x-2-3+3y=-y-1/+5
x+y=5

2x+3y = -y+4/+y
x+y=5

2x+4y = 4
x+y = 5/*(-2)

2x+4y = 4
-2x-2y=-10
____________
2y = -6/2
y=-3
x-3 = 5/+3
x=8
y=-3

d)
4(x+2)=1-5y
3(y+2)=-2x

4x+8 = 1-5y
3y +6 = -2x/+2x

4x+8 = 1-5y
2x+3y+6 = 0/-3y

4x+8 = 1-5y-1
2x+6 =-3y/*(-2)

4x+7 =-5y
-4x-12 =6y
_________
-5 = y

y=-5
4x +7 = 25/-7
4x = 18
x= 4,5
y=-5
2010-02-14T16:06:21+01:00
A)
x+2y=5
3x-y=1

x+2y=5
3x-y=1 /*2

x+2y=5
6x-2y=2
+----------
7x=7 / :7
x=1

x=1
x+2y=5

x=1
2y=5-1

x=1
2y=4 /2

x=1
y=2

b)
x+7y=6
½x-2,4y=3

x+7y=6 / *(-0,5)
½x-2,4y=3

-0,5x-3,5y=-3
0,5x-2,4y=3
+---------------
-5,9y=0 /-5,9
y=0

y=0
x+7y=6

y=0
x=6-7

y=0
x=-1

c)
2(x-1)-3(1-y)=-y-1
x+y=5

2x-2-3+3y=-y-1
x+y=5

2x+4y=4
x+y=5 / *(-2)

2x+4y=4
-2x-2y=-10
+------------
2y=-6 /:2
y=-3

y=-3
x+y=5

y=-3
x=5+3

y=-3
x=8

d)
4(x+2)=1-5y
3(y+2)=-2x

4x+8=1-5y
3y+6=-2x

4x+5y=1-8
3y+2x=-6

4x+5y=-7
2x+3y=-6 /*(-2)

4x+5y=-7
-4x-6y=12
+------------
-1y=5 /:(-1)
y=-5

y=-5
3(y+2)=-2x

y=-5
3y+6=-2x

y=-5
2x=-6+15

y=-5
2x=9 / :2

y=-5
x=4,5

uwielbiam równania